Changing patterns and determinants of transportation carbon emissions in Chinese cities. (1st May 2019) - Li, Fangyi; Cai, Bofeng; Ye, Zhaoyang; Wang, Zheng; Zhang, Wei; Zhou, Pan; Chen, Jian
Abstract: Regional disparities in transportation emissions at the city level in China are of vital importance for future policymaking; however, such studies are insufficient. After estimating the carbon emissions of transportation in China's 341 cities, this study analyzed the spatial pattern evolution of transportation carbon emissions (TCEs) in China from 2005 to 2015. The results revealed that TCEs by roads, water, and aviation increased by 6.6%, 6.2%, and 9.3%, respectively, each year, but those by railways decreased. Moreover, total TCE distribution was found to vary greatly spatially, being significantly lower in central and western cities than in eastern cities. Increases in TCEs in the studied period were primarily from eastern and southwest regions and mainly from roads, although aviation TCE increased significantly in large cities. Based on index decomposition analysis of major cities from the perspectives of population, per capita GDP, TCEs per GDP and TCEs structure, per capita GDP was the most important factor influencing emission growth, followed by population growth; however, TCEs per GDP were a determinant of emission reduction. Finally, all cities were classified into five types based on TCEs' determinants. The results highlight the significant regional disparity and inequity in TCEs at the city level. Highlights: Transportation carbon emissions (TCEs) in 341 cities of China were estimated. TCEs were significantly lower in central and western cities than in eastern cities. TCEs associated with roads, water and aviation increased quickly from 2005 to 2015. Spatial inequalities of road, railway and water TCEs were promoted. TCEs per GDP change leaded to TCEs reduction, while per capita GDP to growth.